Molecular subtyping of paediatric medulloblastoma by immunohistochemistry - Wong, Yin Ping; Loh, C-Khai; Hamidah Alias; Nur Maya Sabrina T; Muaatamarulain M; Tan, Geok Chin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Four core molecular subgroups of medulloblastomas have recently been introduced disparate by their transcriptional profile, all of which have different prognostic value. We aimed to determine the histological variants and molecular subtypes of medulloblastomas by immunohistochemistry in our population, and to correlate that with clinicopathological parameters. Seventeen patients aged four-month to 14.3 years diagnosed with medulloblastoma were recruited from year 2002 to 2017. All medulloblastomas were assigned to various histological variants and molecular subgroups by immunohistochemistry surrogate markers (YAP-1 and beta catenin). They were then correlated with clinicopathological parameters and outcomes. Classic histology (76.5%) was the commonest, followed by large cell/anaplastic (LCA) (17.6%) and desmoplastic/nodular (DN) variants (59%). The most frequent molecular subgroup was non-SHH/WNT tumours (64.7%), seconded by SHH tumours (35.3%). Among the SHH tumours, 66.7% was classic histology and the remaining 33.3% was LCA variant. Interestingly, one DN histology demonstrated YAP-1 and beta catenin immunonegativity, denoting non-SHH/WNT molecular subgroup. Majority (88.2%) medulloblastomas were at midline 4th ventricle location, including DN variant. Estimated three-year diseasefree-survival (DFS) and overall-survival (OS) was 60% and 86.7%, respectively. Age <3 years at diagnosis, tumour size >5 cm, LCA histology and high risk group were inversely correlated with DFS, with early relapse. Infant <3-year-old had worse OS. Other factors had no significant impact on DFS and OS. We had demonstrated the feasibility of simple immunohistochemistry-based surrogate markers (YAP-1 and beta catenin) to stratify medulloblastomas into distinct molecular subtypes. Prognostic and predictive values of YAP-1 immunomarker in medulloblastomas however await further investigations.